Wykonaj działania :

a) √250 + ⁴√10² - ⁶√64 * 10³
b) 3 ³√5 + 6 ⁶√25 + 9 ⁹√-125

Rozwiąż równania :

a) 12 - 2(x-1)² = 4(x-2)- (x-3)(2x-5)
b) (3x - 1)² - 5 (2x+1)² + (6x - 3)(2x+1) = (x - 1)²
c) 2x² + (x+5)² -2(x+7)² = 2(3x - 72,5) + (x - 6)²

1

Odpowiedzi

2009-12-05T10:12:55+01:00
Rozwiąż równania :

a) 12 - 2(x-1)² = 4(x-2)- (x-3)(2x-5)= 12-2(x²-4x+4)-(2x²-5x-6x+15)=
12- 2x²+8x-8-2x²+5x+6x-15=19x-4x²-11

b) (3x - 1)² - 5 (2x+1)² + (6x - 3)(2x+1) = (x - 1)²= 9x²-6x+1-5(4x²+4x+1)+ 12x²+6x-6x-3=9x²-6x+1-20x²-20x-5+12x²+6x-6x-3= -26x+x²-7

c) 2x² + (x+5)² -2(x+7)² = 2(3x - 72,5) + (x - 6)²
2x²+ x²+10x+25-2(x²+14x+49)= 6x- 145+ x²-15x+36
2x²+ x²+10x+25-2x²-28x- 98= 6x- 145+ x²-15x+36
2x²+ x²+10x-2x²-28x -6x-x²+15x= -145+36-25+98
-9x= -36 |:(-9)
x= 4